2021
DOI: 10.1051/e3sconf/202127501002
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Development Path of State-owned Economy - Evidence Based on The Impact of COVID-19 on The Development of Chinese State-owned Industrial Enterprises and Their Post-epidemic Recovery from Financial Perspective

Abstract: Since the spread of the COVID-19, State-owned industrial enterprise have faced many problems such as industrial and supply chain breaks, shutdowns and insufficient production capacity, which are common in the state-owned economy. Financial indicators can often better dig out the economic problems behind them, so we screened 20 relevant composite financial indicators including asset yield, return stability, debt solvency, cumulative profitability, liquidity, capitalization, and scale. After correlation analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…In addition, Horvát et al (2023) found that Heckman's two-variable model (speed and diversity of opinion) predicts who is funded and who repays the financial outcome. Using correlation analysis, Li and Tan (2021) described that the ARIMA model predicts the actual value using the "Operating income growth rate" indicator.…”
Section: Literature Review and Hypotheses Development Predict Innovat...mentioning
confidence: 99%
“…In addition, Horvát et al (2023) found that Heckman's two-variable model (speed and diversity of opinion) predicts who is funded and who repays the financial outcome. Using correlation analysis, Li and Tan (2021) described that the ARIMA model predicts the actual value using the "Operating income growth rate" indicator.…”
Section: Literature Review and Hypotheses Development Predict Innovat...mentioning
confidence: 99%